THE EFFECT OF PACKAGING, SATISFACTION AND IMAGE ON CUSTOMER LOYALTY OF THE EL RAYHAN COMPANY - El Gammudi, Ahmed Khaled; Salim, Ubud; Sabil, Ananda (Accounting Department,, 2016)
This study is aimed at investigating the effect of packaging, satisfaction, and image on customer loyalty to The El Rayhan Company, Libya. The questionnaires are employed to collect the data. The resultreveals that packaging has a positive effect on customer loyalty. Moreover, satisfaction and image affect directly on customer loyalty. However, the highest effect in this study is the packaging effect on customer loyalty.